2011
DOI: 10.1371/journal.pone.0014692
|View full text |Cite
|
Sign up to set email alerts
|

Differential Proteomic Analysis of Platelets Suggested Possible Signal Cascades Network in Platelets Treated with Salvianolic Acid B

Abstract: BackgroundSalvianolic acid B (SB) is an active component isolated from Danshen, a traditional Chinese medicine widely used for the treatment of cardiovascular disorders. Previous study suggested that SB might inhibit adhesion as well as aggregation of platelets by a mechanism involving the integrin α2β1. But, the signal cascades in platelets after SB binding are still not clear.Methodology/Principal FindingsIn the present study, a differential proteomic analysis (two-dimensional electrophoresis) was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…Furthermore, nine components were screened in Fufang Danshen formula based on network pharmacology, which could modulate 42 cardiovascular-associated genes [25]. Additionally, by integrating the above research approaches, it was demonstrated that salvianolic acid B was compatible and feasible for cardiovascular disease treatment [26]. …”
Section: Research Approaches Of Network Pharmacologymentioning
confidence: 99%
“…Furthermore, nine components were screened in Fufang Danshen formula based on network pharmacology, which could modulate 42 cardiovascular-associated genes [25]. Additionally, by integrating the above research approaches, it was demonstrated that salvianolic acid B was compatible and feasible for cardiovascular disease treatment [26]. …”
Section: Research Approaches Of Network Pharmacologymentioning
confidence: 99%
“…Chaperone proteins such as protein disulfide isomerase (PDI), ER oxidoreductin 1␣ (Ero1␣), ER protein 57 (ERp57), and ER protein 5 (ERp5) have emerging roles in regulating the activities of platelets and other hematopoietic cells (20,21,38,55). However, while both Hsp70 and Hsp90 family members have been identified in platelets (31,36,42,48), specific roles for Hsp70 activity in platelet function and aggregate formation have not been addressed.Here we investigate the role of Hsp70 in platelet function. We find that platelets express abundant Hsp70 protein and that Hsp70 localizes throughout platelets, while partially colocalizing with other chaperones such as Hsp90 and PDI.…”
mentioning
confidence: 99%
“…Among various techniques used in platelet proteomics, gel-free and iTRAQ together with MS or LC-MS/MS, 2-DE coupled to kinds of MS were frequently applied to characterize platelets in cardiovascular diseases and in exploring effects of antiplatelet drugs (Coppinger et al 2007;Arias-Salgado et al 2008;Parguiña et al 2010Parguiña et al , 2011L opez-Farr e et al 2011). One of the application of 2-DE coupled to MS is to identify the expression of platelet proteins and suggest the possible signalling pathways after treated with traditional Chinese medicines (TCMs) and active compounds, such as Panax notoginseng (Burkill) F. H. Chen (Araliaceae) (Yao et al 2008b), salvianolic acids (Yao et al 2008a) and salvianolic acid B (Ma et al 2011) from Salvia miltiorrhiza Bunge (Labiatae).…”
Section: Research Articlementioning
confidence: 99%